Strategi Rumah Yatim Ar-Rahman Kota Medan Dalam Pengoptimalisasian Dana Zakat, Infaq dan Shadaqh - Muhammad Rizki Maulana; Muhammad Ridwan (ManBiz: Journal of Management and Business, 2024)
This research is about strategies and optimizing the management of zakat, infaq and shadaqah at the Ar Rahman Orphanage in Medan City. This study started from the author's observations of social care embodied by zakat, infaq and sadaqah as a form of a Muslim's faith to help ease the burden of Muslims, thus making the Muslims prosperous. The purpose of this research is to find out the constraints and efforts as well as strategies in optimizing ZIS funds. The method used in this study uses a descriptive method, namely by collecting interview data, observation, and documentation studies. The results of the study show that the Ar-Rahman Orphanage in Medan City in the strategy of increasing fundraising has 3 strategies, namely the first program strategy which consists of 7 main programs, namely humanitarian programs, orphans and poor self-reliance programs, da'wah programs, educational programs, economic programs, utilization programs, and health programs. In addition to these programs in the Infaq Sadaqah program there is one program called Ifsoh bound. . The obstacles faced in implementing the marketing strategy of the Ar-Rahman Orphans House in Medan City, are the lack of knowledge about zakat in the community, then many people do not understand zakat, infaq, alms through the Orphans and Dhuafa Institutions. Keyword : Dhuafa Orphanage, Strategy, ZIS